Numerical Simulation Analysis of Slope Instability and Failure of Limestone Mine in Weibei. (21st October 2021) - Liu, Kuiming; Li, Hui; Pang, Shihui; Mi, Meng; Chen, Jianping; Sun, Kui
Abstract : Weibei area is the largest limestone resource area in Shaanxi Province, which is an important boundary to distinguish the climate difference between the south and the north of China, and also a significant ecological safety protection barrier in the northwest of China. The complex geological environment and harsh environment make the mining area have serious geological disaster hidden danger. Based on the site engineering geological data of typical limestone quarry slope in Weibei, this paper constructs a three-dimensional geological model, uses FLAC3D software to simulate excavation, and analyzes the stress and strain law of the quarry slope. SlopeLE software was used to analyze the safety factor of slope stability and the potential slip surface before and after taking reinforcement measures. The results show the following: (1) Limestone is the main rock component of the mine, followed by mudstone. The joint and fissure are developed, the rock mass is broken, and the hidden danger of engineering geological disaster is high. (2) There is a sliding trend in both sides during excavation, and the maximum vertical displacement is 2.1 cm. (3) If the slope is reinforced according to the design scheme, the slope stability safety factor will be increased from 1.062 to 1.203 in a stable state, which greatly improves the stability of the slope and provides a guarantee for human and financial resources.